Strategi Digitalisasi dan Branding Produk HoldnGo dalam Pengembangan Usaha Aksesori Non-Iritan: Studi Kasus Nata Ati by Ayunda Karanganyar - Tantiana Tantiana; Didit Purnomo (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyze the development strategy of micro, small, and medium enterprises (MSMEs) through the integration of digitalization, branding, and product innovation focused on safety and sustainability. A case study was conducted on HoldnGo, an MSME producing skin-friendly accessories made from hypoallergenic materials such as organic cotton thread and BPA-free resin. The research employed a Participatory Action Research (PAR) method through the Wirausaha Merdeka (Independent Entrepreneurship) program, involving direct collaboration with internship partner Nata Ati by Ayunda. The findings indicate that the use of non-irritating materials offers a unique differentiation advantage aligned with current self-care and sustainability trends. Furthermore, the digital marketing strategy was enhanced through keyword analysis using the WordStream platform. For instance, the keyword “phone strap” reached a high monthly search volume of 27,100 with a competition index of 69 and relatively affordable top page bid costs. The integration of product innovation and data-driven SEO marketing proved effective in expanding market reach while strengthening brand identity. These results offer a strategic model that can be replicated by other MSMEs to remain competitive in the increasingly dynamic digital marketplace.